PRE-SCHOOL TEACHERS’ ATTITUDES TOWARDS IMPACT OF ICT ON STUDENTS - Bilbokaitė-Skiauterienė, Ieva; Bilbokaitė, Renata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The application of ICT in today’s context of constant change and sustainable development of mankind is a necessity, expressed in the importance, timeliness and meaning of its integrity in the educational process for children. The latter acquire the knowledge needed for the use of ICT more deeply than adults and can easily apply it to various activities. Computer literacy is one of key aspects of societal development, ensuring the need for ICT skills for the present and future. In the face of the Covid-19 pandemic and the challenges of distance learning and teaching, the researches into the interaction of children with ICT, and especially the importance of computer games for the development and education of children, is becoming of paramount importance.The study aims to reveal the attitudes of pre-school teachers towards impact of ICT and computer games on students. The results of the research, based on the assumption, represent the attitudes of teachers on the application of ICT tools in pre-school education. A qualitative approach was applied to the study – focus groups with 48 pre-school teachers. The results of the research reveal that the ICT and computer games has significant impact on preschool children in the self-learning process, by changing their knowledge, skills, behaviour and attitudes.